STRATEGI TIONGKOK MEMBENDUNG DOMINASI ASTROPOLITIK AMERIKA SERIKAT PASCA PERCOBAAN SENJATA ANTI-SATELIT TIONGKOK 2007 - Abimanyu Perkasa Setiawan; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to explain how Tiongkok's strategy to containt the astropolitical domination of the United States. This is an action-reaction form of the United States boycott of Tiongkok in cooperation in the field of space technology development. In 2011, the United States banned all forms of space cooperation with Tiongkok, this policy was triggered by the testing and development of anti-satellite weapons (ASAT) conducted by Tiongkok in 2007. These weapons tests coincided with the rise of Tiongkok's capability to develop space technology both for peaceful purposes or for militarization purposes that could threaten the dominance of the United States in this field. This study uses a neorealism perspective and explained by the level of analysis of the nation state, in this case, between the United States and Tiongkok. This study uses strategic theory which is considered to be able to explain how Tiongkok's steps can containt the domination of the United States itself. The data that the author collects as a reference in compiling this research comes from books, journals, articles, websites, news sites, publications, and previous research. With the development of cutting-edge technology such as 'Tiangong' space station, exploration of the outer planets, deep space observation technology, and the development of space weapons, Tiongkok can be said to have been able to match the power of the United States as one of the pioneers of space technology, for the better, all the technology developed by Tiongkok is relatively done independently. Keywords: United States, Tiongkok, Domination, Astropolitics, ASAT, Technology, and Strategy